The Adhyatma Ramayana: An Integrative Framework for Holistic Personality Development and Spiritual Transformation - Pallathadka, Harikumar; Roy, Parag Deb (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The Adhyatma Ramayana, attributed to sage Vyasa and considered a significant component of the Brahmanda Purana, represents a sophisticated framework for human development that merges spiritual wisdom with psychological transformation. This research synthesizes textual analysis, comparative religious studies, and psychological theory to establish how this classical Sanskrit text functions as a comprehensive system for personality development. Through rigorous hermeneutical analysis of its seven kandas (sections) and preliminary studies, we demonstrate how engagement with the text's principles correlates with improvements in psychological well-being, emotional regulation, and moral reasoning capability. Our interdisciplinary framework reveals how the Adhyatma Ramayana integrates constructivist learning, archetypal psychology, contemplative neuroscience, and developmental systems theory to create a coherent development model applicable across cultural contexts. This research contributes to the growing field of contemplative science by exploring traditional wisdom practices and their potential applications for contemporary education, psychotherapy, leadership development, and personal growth.